Engineering high-entropy materials for electrocatalytic water splitting - Yang, X.; Guo, R.; Cai, R.; Ouyang, Y.; Yang, P.; Xiao, J.
The multicomponent combinations of metals in nanoscale noble metal-free high-entropy materials possess distinctive physiochemical properties, which endow them with rich accessible active sites, strong synergistic effect, and entropy-stabilization effect, enabling them to be promising for driving electrocatalytic water splitting. Herein, an interview of the progress achieved for the synthesis of noble metal-free high-entropy materials and catalytic mechanisms toward water splitting is provided. Some typical synthesis strategies have been systematically reviewed to highlight the advances in synthesizing highly efficient and noble-metal-free high-entropy catalysts. Next, the distinctive advantages of high-entropy materials for the electrochemical water splitting are also manifested to show their great promise for serving as advanced electrocatalysts. Moreover, some representative examples regarding the electrocatalytic oxygen evolution reaction, hydrogen evolution reaction, and overall water splitting based on noble-metal-free high-entropy catalysts are also discussed. In the end, future directions and new energy conversion technologies that can be enabled by the application of noble-metal-free high-entropy materials are outlined.
Keywords: NOBLE METAL-FREE; HIGH-ENTROPY; ELECTROCATALYSIS; WATER SPLITTING